Morality in the Populist Radical Right: A Computer-Assisted Morality Frame Analysis of a Prototype - Vossen, Job P.H. (Politics of the Low Countries, 2025)
This article provides a computer-assisted morality framing analysis of Vlaams Belang’s 2019 manifesto. The VB is regarded in the literature as a prototypical example of the Populist Radical Right (PRR). We first concisely review what PRR politics is and what it consists of, tentatively distinguishing four elements that we hypothesise will materialise in corresponding subframes running throughout the manifesto. We point to a mismatch between the omnipresent role of morality in all PRR subframes and the little attention devoted to the concept in the PRR literature. We introduce a useful theory from social psychology into framing literature to create a novel methodological approach to frame analysis that builds a bridge between a qualitative content and a quantitative context approach. The results support our hypothesis that populism, nationalism, nativism and authoritarianism can be distinguished from one another. Additionally, we detect a fifth PRR subframe, crimmigration, by its unique role of morality.